Temporal and spatial variations for petroleum hydrocarbons in water and sediments from Northern parts of Shatt Al-Arab River, Iraq - Al-Imarah, F.J.M.; Ali, S.A.; Ali, A.A. (Mesopotamian Journal of Marine Sciences, 2022)
Regional and temporal distribution of Total Petroleum Hydrocarbons (TPH’s) and percent Total Organic Carbon (TOC %) were investigated in water and sediments from 5 stations along Shatt Al-Arab river (1-Qurnah, 2-Shafi, 3-Deer, 4-Nihran Omer and 5-Sinbad close to expected sources of pollution by petroleum hydrocarbons. Measured TPH’s in the dissolved phase of water were ranged between 5.10 ng/l in station 3 and 9.48 ng/l in station 5 comparable to Basrah light crude oil. In the sediments levels of PHC’s ranged between 7.37 mg/l in station 3 and 24.41 mg/l in station 5.Seasonal variations in TPH’s in waters and sediments were found as lower concentrations 2.65–4.20 and 3.15–10.36 mg/l respectively during summer, while higher concentration recorded during winter were found to be 7.86–15.60 µg/l in water and 13.52–45.21 mg/g in sediments. % TOC measured in the sediments were ranged from 0.50 % to 0.81 % in stations 2 and 5 respectively. Strong positive correlations were found between TPH’s and TOC for all stations with correlation coefficient (r = 0.93).